The five practices of exemplary leadership : government - Kouzes, James M., 1945- (Pfeiffer, 2011)
This 24-page article is perfect for leaders with limited time and budget. It provides a concise overview of Kouzes and Posner's model and overall thoughts on leadership in the realm of government/public sector. Ideal for orienting readers to the Five Practices® model at the beginning of a workshop or coaching session, the piece contains two Leadership Challenge case studies drawn from government and the public sector, a short description of the Five Practices®, a section on "Learning to Lead", and background information on the Leadership Practices Inventory (LPI).